The teaching of the biotic community concept with the Balara amphitheater site as the model - Medina, Zonia T. 1940- (s.n.], 1965)
This paper promotes the knowledge and understanding of the biotic community concept by providing a model which biology teachers may use for teaching the concept in their own communities. The author presented the two major approaches of teaching biology-- the traditional and the modern.